Comparative Study of Risk Factors Between Lacunar and Non-lacunar Ischemic Strokes (Bangladesh Journal of Neuroscience, 2013)
Background: Stroke is a leading cause of mortality and morbidity in both developed as well as developing countries The risk factors in lacunar stroke differ in comparison to nonlacunar strokes. In this study risk factors of lacunar stroke in comparison to non-lacunar were evaluated. Objectives: The aim of the study was to compare the risk factors among lacunar stroke and non-lacunar stroke. Methodology: This comparative study conducted in the department of Medicine and Neurology, Dhaka Medical College Hospital, Dhaka from September 2010 to August 2011. MRI of brain was done in 151 patients above 18 years of age with ischemic stroke and Lacunar stroke was found in 31 patients and non-lacunar stroke was detected in 120 patients. Based on the inclusion and exclusion criteria from them 30 patients with lacunar stroke were selected as Group-A patients and equal number of non-lacunar stroke same ages as group B were compared of. The risk factors of stroke were defined as hypertension, diabetes mellitus, hypercholesterolemia, smoking, history of transient ischemic attack, myocardial infarction, atrial fibrillation and carotid artery stenosis. Results: Out of 151 patients with ischemic stroke non-lacunar stroke was predominant, which was 79.47% and lacunar stroke was 20.52%. The mean age was found 60.9±10.2 years in Group A and 56.2±11.8 years in Group B, which was almost similar between two groups (p>0.05). Male were predominant, which was 63.33% and 76.67% in lacunar and non-lacunar stroke respectively. Male and female ratio was 2.3:1. Regarding the risk factors hypertension was observed most common risk factor among the patients having lacunar and non-lacunar strokes. Hypertension and diabetes mellitus were common in lacunar stroke and myocardial infarction, carotid artery stenosis and hypercholesterolemia were common in non-lacunar stroke which were statistically significant (p0.05) different between lacunar and non-lacunar stroke. Conclusion: Hypertension and diabetes mellitus were common in lacunar stroke, and myocardial infarction, whereas carotid artery stenosis and hypercholesterolemia were common in non-lacunar stroke and the both groups were statistically significant (p